2018
DOI: 10.1007/s00420-018-1339-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation, mechanisms and effects of maternity protection legislation: a realist narrative review of the literature

Abstract: This study showed the need for a better implementation of MPL during pregnancy. Further research and recommendations for improvements in MPL should consider the diverse mechanisms and effects of its implementation. Barriers and adverse effects of this implementation do not only ensure a lack of information or awareness about MPL, but are also linked to contradictions between requirements to protect employment and protect pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
(106 reference statements)
1
23
0
3
Order By: Relevance
“…The latter practice weakens the law as an incentive for companies to develop internal preventive strategies. Similar findings were also highlighted by the authors in a recent international literature review, 19 inspired by Bronfenbrenner’s ecological model 20 and realist approaches, 21 which revealed the many levels of difficulty and complexity in introducing MPL: (1) the lack of knowledge about the legal provisions concerning occupational maternity protection, on the part of employees as well as employers, can have an impact on the implementation of appropriate measures; (2) at the organisational and social levels, the company’s status, the collaboration between the different stakeholders and the way in which the notion of risk is defined within a company also play a role; and (3) at the societal level, the implementation of MPL depends largely on political incentives, the standing which women have in their company and knowledge about professional risks.…”
Section: Introductionsupporting
confidence: 90%
“…The latter practice weakens the law as an incentive for companies to develop internal preventive strategies. Similar findings were also highlighted by the authors in a recent international literature review, 19 inspired by Bronfenbrenner’s ecological model 20 and realist approaches, 21 which revealed the many levels of difficulty and complexity in introducing MPL: (1) the lack of knowledge about the legal provisions concerning occupational maternity protection, on the part of employees as well as employers, can have an impact on the implementation of appropriate measures; (2) at the organisational and social levels, the company’s status, the collaboration between the different stakeholders and the way in which the notion of risk is defined within a company also play a role; and (3) at the societal level, the implementation of MPL depends largely on political incentives, the standing which women have in their company and knowledge about professional risks.…”
Section: Introductionsupporting
confidence: 90%
“…The model takes into consideration multiple dimensions that affect work performance: staff characteristics, symptoms, health and well-being, functions, work demands, and work environment [30]. This complexity is further described in relation to pregnancy in a narrative review [18] investigating implementation of the maternity protection legislation in industrialized countries and its expected and unexpected effects. The review stresses the importance of viewing maternity protections in a broader context, and its implementation to progress in the future [18].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies based on interviews with working pregnant women find that the pregnant women lack awareness and consideration of their pregnancy at work [16,17]. Managers were considered the most significant stressor at work, because of a negative attitude towards the occurrence of pregnancy [17,18]. There is a lack of studies identifying these issues from a managerial point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The purposes of this Ordinance are in conformity with International Labour Organization Recommendation 191 on maternity protection [22]and with the Council Directive 92/85/EEC of 19 October 1992 [23]. The literature review conducted by Probst, Zellweger [24]provides a comparison of features of maternity protection legislation in different countries. The OProMa stems from the Swiss Labor Law (LTr, section 35), which defines a general framework for the protection of the health of pregnant workers [20,25].…”
Section: The Swiss Legal Framework Concerning the Protection Of Pregnmentioning
confidence: 99%
“…Numerous studies have demonstrated shortcomings in the application of countries' MPL, in different contexts and at different levels [24]. Furthermore, in contexts where OBGYNs play a role in the application of MPL, it has been shown that they do not necessarily feel competent to judge working conditions and pregnant women's ability to work [31,32].…”
Section: Disparities Between Obgyns' Practices and Those Provided Formentioning
confidence: 99%